Another tasty combination. - Curthoys, Paul (Mac life)
Forget oil and water-these days, OS X and Windows 7 go together like cookies and milk. We'll help you savor both flavors with an in-depth look at the most cutting-edge ways to run these two operating systems on one Mac.